Antacid therapy and disease outcomes in idiopathic pulmonary fibrosis: a pooled analysis - Kreuter, Michael; Wuyts, Wim; Renzoni, Elisabetta; Koschel, Dirk; Maher, Toby M; Kolb, Martin; Weycker, Derek; Spagnolo, Paolo; Kirchgaessler, Klaus-Uwe; Herth, Felix; Costabel, Ulrich (The lancet. Respiratory medicine, 2016)
Background - Gastro-oesophageal reflux disease is a potential risk factor for the development and progression of idiopathic pulmonary fibrosis (IPF). We aimed to investigate the effect of antacid therapy on disease progression in patients randomly assigned to placebo through analysis of three large, phase 3 trials of pirfenidone in IPF. - Methods - Patients with IPF from the placebo groups of three trials of pirfenidone (CAPACITY 004, CAPACITY 006, and ASCEND) were included in this post-hoc analysis. We analysed effects of antacid therapy use from baseline for pulmonary function, exercise tolerance, survival, hospital admission, and adverse events for 52 weeks with and without adjustment for potential confounders. The primary endpoint, disease progression by 1 year, was defined as a decrease in predicted forced vital capacity (FVC) by 10% or more, a decrease in 6 min walk distance (6MWD) by 50 m or more, or death. We did survival analyses with the Kaplan-Meier estimator and evaluated using the log-rank test. - Findings - Of 624 patients, 291 (47%) received antacid therapy and 333 (53%) did not. At 52 weeks, we noted no significant difference between groups for disease progression (114 [39%] for antacid therapy vs 141 [42%] for no antacid therapy, p=0·4844). Rates also did not differ for all-cause mortality (20 [7%] vs 22 [7%], p=0·8947), IPF-related mortality (11 [4%] vs 17 [5%]; p=0·4251), absolute FVC decrease by 10% or more (49 [17%] vs 64 [19%]; p=0·4411), or mean observed change in FVC (% predicted −4·9% [SD 6·4] vs −5·5% [7·2], p=0·3355; observed volume −0·2 L [0·3] vs −0·2 L [0·3], p=0·4238). The rate of hospital admission was non-significantly higher in the antacid therapy group (65 [22%] vs 54 [16%]; p=0·0522). When stratified by baseline FVC (<70% or ≥70%), disease progression, mortality, FVC, 6MWD, and hospital admission did not differ between groups. Adverse events were similar between treatment and no treatment groups; however, overall infections (107 [74%] vs 101 [62%]; p=0·0174) and pulmonary infections (20 [14%] vs 10 [6%]; p=0·0214) were higher in patients with advanced IPF (ie, FVC <70%) who were treated with antacids than not treated with antacids. - Interpretation - Antacid therapy did not improve outcomes in patients with IPF and might potentially be associated with an increased risk of infection in those with advanced disease. - Funding - F Hoffmann-La Roche.
Gesehen am 28.05.2020